Analytical methods of phytochemicals from the Cuphea genus - A review - Marí Castro Santos; Amélia Teresinha Henriques; Andreas Sebastian Loureiro Mendez (Drug Analytical Research, 2021)
Cuphea genus (Lythraceae) comprises about 260 species. The dispersion of the genus occurs in two mains geographic centers: North and South America, with Brazil being the most Cuphea species-rich country, with approximately 104 identified species. Still poorly studied, the number of papers about genus has been growing considerably. However, a review of its analytical methods has not been previously performed. Therefore, this review aims to provide studies about different chromatographic methods used for the separation, elucidation, and identification of metabolites present in species of the Cuphea genus. Research in scientific databases like Scopus, PubMed, and Science Direct were managed, and all references were analyzed. This review covers the relevant literature until May 2021, totalizing 22 studies described on 12 species of Cuphea. Most methods were employed for chemical analysis, and just one of them was validated for quantification purposes. Thus, this review provides a brief overview of the different chromatographic methods used in the separation, elucidation, and identification of compounds on different species of the Cuphea genus.